Post-COVID Reflections, the Dental Laboratory Perspective - Anamelechi, C. A. (Nigerian Dental Journal, 2023)
There has been a growing interest in the topic of COVID-19 and its impact on dental laboratories. It has gained attention from researchers, policymakers, and the public due to its significance for the overall safety of dental practitioners. Understanding the various aspects of this topic is crucial to addressing the challenges and opportunities it presents. This paper will delve into the different dimensions of the pandemic’s impact and explore its implications for the future of dental technology and dentistry at large. The purpose of the paper is to provide a comprehensive analysis of COVID-19 and its impact on the practice of dental technology. By examining the different perspectives and factors involved, we aim to offer insights and recommendations for addressing the issues and leveraging the opportunities associated with them. Lessons learned from the pandemic can be applied to future crises. The importance of preparedness, adaptability in navigating uncertain times and strategies for adapting to future crises will be highlighted.